Internet Content-based Activities for Empowering Listening Comprehension to the First Semester Students of English Department State Polytechnic of Sriwijaya Palembang - Yusri Yusri (Universitas PGRI Palembang, 2015)
AbstractThis study was conducted to find out (1) whether or not it is effective empowering students’ listening comprehension through Internet Content-Based Activities. The samples of this study were the first semester students of English Department State Polytehcnic of Sriwijaya Palembang in the academic year of 2013-3014. The primary data were collected by means of test. The results show that there was a statistically significant difference in listening comprehension achievement of the students pretest-posttest after being taught through Internet Content-Based Activities. It was found out that the average score of the students’ pre- test was 65.33 while in the post test was 74.19. the result of t-test calculation shows that the value of t was 6.472. Where the value of the t-table 2.086 at the significance level of 0,05% with df 20. Thus, t-obtained was higher than t-table. It can be concluded that Internet Content-Based Activities was effective empowering the first semester, English department students’ listening comprehension at State Polytechnic of Sriwijaya Palembang. Key Words : Internet Content-Based Activities, Listening Comprehension